Karakteristik dan Perilaku Ibu dalam Memberikan Stimulasi Perkembangan pada Anak Usia 18-24 Bulan - Nur Windiya; Lili Fajria; Meri Neherta (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Providing education is the effort for promotif and prevntif for mother to give growth stimulation children 18-24 month. This research is a descriptive study that aims to explore the characteristics and behavior of mother for give growth stimulation children 18-24 month. This is done to be able to plan the provision of further interventions to mother have children 18-24 month. The sampling technique used probability methods with a clustersampling technique totaling 41 respondents. The research instrument used KAP (Knowledge, Attitudes, and Practices) with a total of 32 questions, Cronbach alpha knowledge (0.542-0,871), attitude (0.521-0.658), and action (0.452-0.713). Data analysis using univariate analysis. Characteristics of respondents at the age of 26-35 years (85.4%), most education is high school (48.1%), mother not work (82.9%), the most ethnic is minang (92,7%), the number of children is first (87.8) and acumulation of children is second (87.8%). The mean value of knowledge is 58.54, attitude is with a mean value of 25.24, and practice is with a mean value of 60.24. Based on the conclusion, the results of research on the behavior of mother to give growth stimulation of children 18-24 month is inadequate make delayed and disturbance of growth.